Penggunaan Media Gambar Dalam Meningkatkan Kegiatan Motorik Halus Melalui Stempel Berbahan Alam Dengan Pelepah Pisang Pada Anak Kelompok B di TK Cilukba Tataaran 1 - Jenny I. Dengah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to use image media to improve children's fine motor activities through stamps made from natural materials with banana stems. This research is classroom action research. The use of image media to improve fine motor activities through banana stems is one of the learning processes to help solve problems for children. The use of image media to improve fine motor activities through stamps made from natural materials with banana stems. The research was carried out at the Cilukba Tataaran I Kindergarten on 15 group B children consisting of 8 boys and 7 girls. This classroom action research was carried out in two cycles and meetings were held in each cycle. The results of the research prove that through the media images can improve fine motor activities in using banana stems. The results of research in cycle I of 15 children only reached 40% and in cycle II of 15, it had reached 80% and thus it can be concluded that the use of image media in improving fine motor activities through stamps made from natural materials with banana stems in group B children in Kindergarten Cilukba Tataaran 1 was declared successful